Long-term outcomes among injured older adults transported by emergency medical services. Issue 6 (June 2019) - Newgard, Craig D.; Lin, Amber; Yanez, N. David; Bulger, Eileen; Malveau, Susan; Caughey, Aaron; McConnell, K. John; Zive, Dana; Griffiths, Denise; Mirlohi, Rahill; Eckstrom, Elizabeth
Highlights: Among a population-based cohort of 15, 649 injured older adults transported by 44 EMS agencies to 51 hospitals, 20.3% of patients died within 1 year. The most common causes of death were cardiovascular and dementia, with the majority of deaths occurring after hospital discharge. Comorbidities were common and had an adjusted mortality risk comparable to that of severe injuries. Abstract: Introduction/Objective: Little is known about the long-term outcomes of injured older adults cared for in trauma systems. We sought to describe mortality and causes of death over time, and the independent association of injury severity, comorbidities, and other factors on 12-month mortality among injured older adults transported by emergency medical services (EMS). Materials and Methods: This was a population-based cohort study of injured adults ≥ 65 years in the United States transported by 44 EMS agencies to 51 hospitals from January 1, 2011 to December 31, 2011, with 12-month follow-up through December 31, 2012. The primary outcomes were time to death and causes of death. We used descriptive statistics and Cox proportional hazards models to generate adjusted hazard ratios (HR). Results: 15, 649 injured older adults were transported by EMS, frequently after a fall (84.5%). Serious injuries (Injury Severity Score [ISS] ≥ 16) occurred in 3.5%, with serious extremity injury (Abbreviated Injury Scale score ≥ 3) being most common (17.8%). Mortality rates were: 1.6% in-hospital, 5.1% at 30 days, 9.4% at 90 days and 20.3% at 1 year. The adjusted HR for patients in the highest comorbidity quartile was 2.20 (versus lowest quartile, 95% CI 1.97–2.46, p < .001), while the HR for ISS ≥ 25 was 2.69 (versus ISS 0–8, 95% CI 1.60–4.51, p = .001). Cardiovascular etiologies (53.3%) and dementia (32.7%) were the most common causes of death, with injury listed in 12.8% of death certificates. Conclusions: Injury requiring EMS transport is a sentinel event among older adults, with death typically occurring months later, often due to cardiovascular causes and dementia. A heavy comorbidity burden had an adjusted mortality risk comparable to severe injury.